The Relationship Between Self-Regulation and Academic Procrastination in Grades 7 & 8 Students of Muhammadiyah 8 Middle School Tanggulangin: Hubungan Antara Regulasi Diri dengan Prokrastinasi Akademik pada Siswa Kelas 7 & 8 Sekolah Menengah Pertama Muhammadiyah 8 Tanggulangin - Hasyim, Adji; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to identify and provide an explanation of the relationship between self-regulation and academic procrastination in class VII & VIII students of SMP Muhammadiyah 8 Tanggulangin. This research method is quantitative with the subjects of class VII & VIII students totaling 99 students. Determination of the subject using a saturated sampling technique where sampling is done by considering certain characteristics. The variables in this study were self-regulation and academic procrastination. Data collection in this study used two psychological preparation scales, namely the Likert scale for self-regulation variables and academic procrastination made by the researcher. The hypothesis in this study is that there is a negative relationship between self-regulation and academic procrastination. Analysis of the data in this study using statistical product moment correlation test with the help of SPSS 18 for Windows. The results of this study indicate that there is a negative relationship between self-regulation and academic procrastination in class VII & VIII SMP Muhammadiyah 8 Tanggulangin with a value of r = -0.265 with a significance value of 0.000 (P<0.05). This means that there is a significant negative relationship between self-regulation and academic procrastination in class VII & VIII students of SMP Muhammadiyah 8 Tanggulangin. So, the results of the initial hypothesis that the researcher proposes can be accepted.